1974
DOI: 10.1111/j.1365-2133.1974.tb12945.x
|View full text |Cite
|
Sign up to set email alerts
|

A case of purpura hyperglobulinaemica of Waldenstrom studied by skin immunofluorescence

Abstract: A case of purpura hyperglobulinaemica of Waldenstrom is reported. Immunofluorescence of skin and subcutaneous tissue using monospecific fluorescein-tagged anti-human IgA, IgG, IgM and complement showed deposition of IgA in the walls of intradermal vessel in affected skin. It is suggested that these findmgs help in the elucidation of the pathogenesis of the purpura.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 14 publications
(4 reference statements)
2
7
0
Order By: Relevance
“…This has been confirmed in other cases when immunofluorescent studies of skin biopsies have revealed immunoglobulin infiltration of dermal blood vessels and adjacent connective tissue [12]. Presum ably, removal of excess intravascular po lyclonal IgG retards the degree of vascular infiltration and allows the local inflamma tory response causing the purpuric lesions and joint swelling to regress.…”
Section: Discussionsupporting
confidence: 52%
“…This has been confirmed in other cases when immunofluorescent studies of skin biopsies have revealed immunoglobulin infiltration of dermal blood vessels and adjacent connective tissue [12]. Presum ably, removal of excess intravascular po lyclonal IgG retards the degree of vascular infiltration and allows the local inflamma tory response causing the purpuric lesions and joint swelling to regress.…”
Section: Discussionsupporting
confidence: 52%
“…20 In the treatment of HGPW, it is most likely that MMF's immunosuppressive affects provided benefit by disrupting the formation of immune complexes, which are thought to be the causative factor. 18,19 In our patient, there was a demonstrated decrease in both the gamma globulin and sedimentation rate after therapy was initiated, which was most likely a result of the inhibition of both T and B lymphocytes. There was also a significant improvement in the patient's symptoms that coincided with the normalization of laboratory values.…”
Section: Mycophenolate Mofetil Treatment Of a Patient With Hyperglobumentioning
confidence: 67%
“…[2][3][4][5][6][7][8]10 In support of an autoimmune process, several individual cases and studies have demonstrated the presence of immunoglobulin within blood vessel walls and circulating immune complexes as the most likely cause of HGPW. 8,[10][11][12]18,19 MMF is an immunosuppressive agent with a mechanism of action that has been well described. [13][14][15][16] It has been used to treat a variety of cutaneous inflammatory/autoimmune conditions (Table I) including autoimmune blistering disorders and cutaneous collagen vascular diseases.…”
Section: Mycophenolate Mofetil Treatment Of a Patient With Hyperglobumentioning
confidence: 99%
“…(e) Sedimentation rate of the com plexes between 16S and 19S [2][3][4]8]. (0 Normal levels of complement factors and normal total hemolytic activity [7,8,15].…”
Section: Discussionmentioning
confidence: 99%
“…Even without knowing its etiology, immune mechanisms have been consid ered in the pathogenesis of this syndrome, because of the constant presence of circu lating immune complexes (CIC), with sed imentation rate between 7S and 19S [2,3], composed of IgG-anti-IgG [4], and/or IgA-anti-IgG [5,6]. Furthermore, immu nofluorescence studies of involved areas of the skin revealed intradermal deposits of the same Ig classes [7,8]. In order to de monstrate CIC with different chemical, physical and biological characters, which could mediate the disease, we examined the sera of 7 patients with HPW, studying the immunoglobulin concentration, the complement factors, the rheumatoid activ ity, the presence of CIC and their compo sition.…”
mentioning
confidence: 99%